MAKNA BERHIJAB BAGI MUSLIMAH: SEBUAH PERSEPSI MAHASISWI FISIP UNIVERSITAS MUHAMMADIYAH KENDARI - Patta Hindi Asis (Jurnal Dakwah Tabligh, 2017)
Hijab is symbolyzed as marker modesty for moslem’s women. Over time, it is not only seen as a loyalty, but as the existence of women in fashion in a community. In progress, Hijab follows liogic of market which eventually it makes for more fashionable just for business. This research explores of experience moslem’s women using Hijab in a university in Kendari. Using a case study and experience of writer who interacts with student of moslem’s women who wear the veil in a classroom are the method to collect the data. Critical Sociology is used as perspective of this study. This study found that some moslem’s women wear hijab as religous view, and some stated only for lifestyle.